Synthesis and synthetic applications of (4-hydroxyphenyl)perfluoroalkylmethanols. (8th January 2022) - Terashima, Kyu; Kawasaki-Takasuka, Tomoko; Minami, Ichiro; Yamazaki, Takashi
Abstract: Development of the convenient method for the synthesis of (hydroxyphenyl)perfluoro-alkylmethanols was achieved by the Meerwein-Ponndorf-Verley (MPV) type reduction of the in situ -generated perfluoroalkylated ketones as the key step. The benzylic OH group of the resultant alcohols was successfully converted to H or Rf(CH2 )n O by way of the corresponding chlorides, this transformation being not easy by any other methods. Graphical abstract: Image 1